2018
DOI: 10.1096/fj.201700231rr
|View full text |Cite|
|
Sign up to set email alerts
|

Vanillic acid attenuates obesityviaactivation of the AMPK pathway and thermogenic factorsin vivoandin vitro

Abstract: Energy expenditure is a target gaining recent interest for obesity treatment. The antiobesity effect of vanillic acid (VA), a well-known flavoring agent, was investigated in vivo and in vitro. High-fat diet (HFD)-induced obese mice and genetically obese db/db mice showed significantly decreased body weights after VA administration. Two major adipogenic markers, peroxisome proliferator activated receptor γ (PPARγ) and CCAAT/enhancer-binding protein α (C/EBPα), were reduced while the key factor of energy metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 73 publications
(76 reference statements)
4
53
0
Order By: Relevance
“…This is in accordance with Han et al and Jung et al, who previously found vanillic acid to promote thermogenesis in C57BL/6J mice and in primary cultured adipocytes [72,73].…”
Section: Mitochondrial Involvementsupporting
confidence: 93%
“…This is in accordance with Han et al and Jung et al, who previously found vanillic acid to promote thermogenesis in C57BL/6J mice and in primary cultured adipocytes [72,73].…”
Section: Mitochondrial Involvementsupporting
confidence: 93%
“…VA is well-reported to exert anticancer activities in several types of cancers, including lymphocytes [20], leukemia [21], colon cancer [22], lung cancer [23], and also melanoma [19]. Moreover, we showed its anti-obesity effect in our previous study [24]. Since references support the potentially beneficial properties of VA in a comorbid situation of cancer and obesity, under this hypothesis, we establish a cancer-obesity comorbidity model (COC) of melanoma based on a study by Jung et al [7] and investigate the effect of VA focusing on the role of STAT3 pathway.…”
Section: Introductionsupporting
confidence: 52%
“…Two days after tumor inoculation, VA (10 mg/kg/day) was administered via oral gavage every other day, for two weeks, to one of the tumor-injected groups. The dose of VA was determined based on our previous study [24]. All groups were maintained with HFD administration.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Cytotoxicity of BR, SR, and BR-SR mixture was evaluated using the MTS assay, as previously described [23]. The absorbance was measured at 490 nm using a VERSAmax microplate reader (Molecular Devices, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 99%